(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
Objective to study the morphological and functional disorders of the pancreas and blood vessels of the lower limb of rats with experimental diabetes mellitus. The object of the study were 90 white rats at the age of 4-6 months. The morphological changes of the pancreas and the walls of blood vessels of the lower limb in experimental diabetes mellitus. Model of experimental diabetes reproduced by single intraperitoneal administration of streptozotocin Wistar rats at a dose of 60 mg / kg. Comparison of the mass of bodies of rat control and experimental group showed that during the experiment, the experimental group of rats had plenty in development compared to the control group by 1.7 times. In all the experiments in terms of pancreatic islets was observed moderate lymphocytic infiltration. Morphological examination of the vessels in different time postnatal ontogenesis demonstrated that compared with the control group in the form of changes in the delay of progression and formation of individual components vascular wall. Destructive changes in the arterial wall marked us all experimental animals from the early days after the experiment. Conclusion. The results indicate that the type 1 diabetes the pancreas causes changes and limbs.